2021
DOI: 10.1186/s13287-021-02148-5
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical mesenchymal stem cell-derived exosomes facilitate spinal cord functional recovery through the miR-199a-3p/145-5p-mediated NGF/TrkA signaling pathway in rats

Abstract: Background Although exosomes, as byproducts of human umbilical cord mesenchymal stem cells (hUC-MSCs), have been demonstrated to be an effective therapy for traumatic spinal cord injury (SCI), their mechanism of action remains unclear. Methods We designed and performed this study to determine whether exosomes attenuate the lesion size of SCI by ameliorating neuronal injury induced by a secondary inflammatory storm and promoting neurite outgrowth. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(61 citation statements)
references
References 31 publications
1
55
0
Order By: Relevance
“…NGF is a nerve cell growth regulator with dual biological functions of neuron nutrition and neurite outgrowth promotion. It has been proven to protect neurons by promoting nerve fiber regeneration [ 36 , 37 ]. Previous studies have shown that LPS-induced inflammation is the main cause of neuronal death in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…NGF is a nerve cell growth regulator with dual biological functions of neuron nutrition and neurite outgrowth promotion. It has been proven to protect neurons by promoting nerve fiber regeneration [ 36 , 37 ]. Previous studies have shown that LPS-induced inflammation is the main cause of neuronal death in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…MSC-EV fusions have been shown to play critical roles in the intercommunications among brain cells, occurring during health and in various pathologies ( Table 1 ). Numerous protective results have been reported, including development of synaptic plasticity, nutritional metabolic support, nerve regeneration, inflammatory response, and elimination of toxic components [ 46 , 57 ]. Traumas and ischemic lesions can be induced in both the brain and spinal cord.…”
Section: Role Of the Extracellular Vesicles From Mesenchymal Stem Cells: Recent Views About The Alzheimer’s Diseasementioning
confidence: 99%
“…Traumas and ischemic lesions can be induced in both the brain and spinal cord. In many cases, the recovery induced by low doses of MSC-EVs has been shown to start with activation of few receptors, followed by phosphorylation of kinases and various factors, and by activation of miRNAs [ 56 , 57 , 58 , 59 ]. Analogously, MSC-EVs have been shown to mitigate trained immune responses induced by innate cells, with distinct local repair [ 60 ].…”
Section: Role Of the Extracellular Vesicles From Mesenchymal Stem Cells: Recent Views About The Alzheimer’s Diseasementioning
confidence: 99%
“…Among the included 32 studies, only two studies were controlled studies (29,33), and the remaining 30 studies were randomized controlled studies. The species of animals included SD rats (19-21, 28-37, 39, 40, 42-44, 46, 47, 49-53, 55, 56), Wistar rats (41,54), and C57BL/6 mice (38,45,48); gender included male (28, 30-32, 38-45, 49, 53, 54) and female (19, 20, 29, 33, 34, 36, 37, 46-48, 50-52, 55, 56), two studies did not report the sex of the animals (21,35); the weights of animals were between 150 (41) and 300 g (20,44), the weight of the mouse was between 17 and 22 g ( 48), and seven of the studies did not report the weight of the animals (21,29,30,38,42,45,50); age was between 6 (38,44,45,50,51) and 12 weeks (47, 56), and nine of the studies did not report the age of the animals (19, 21, 35-37, 42, 46, 51, 52); samples size were between 10 (51) and 100 (41); models of SCI included contusion (20, 21, 28-32, 34-53, 56), hemisection (54), and transection (19,33,55); the types of exosomes included the exosomes of bone marrow mesenchymal stem cells of SD rats (BMSCs-Exo) (20, 21, 28, 30, 34-37, 39, 42-44, 47, 49, 52, 53, 56), BMSCs-Exo of Wistar rats (41,54), BMSCs-Exo of human (19,33,…”
Section: Basic Information For Inclusion In the Studymentioning
confidence: 99%